Tumor Microenvironment Profiles Reveal Distinct Therapy-Oriented Proteogenomic Characteristics in Colorectal Cancer - Wang, Nan; Wang, Rongshui; Li, Xia; Song, Zhentao; Xia, Lingbo; Wang, Jue; Zhang, Li; Wu, Aiwen; Ding, Zhiyong (Frontiers in Bioengineering and Biotechnology, 2021)
Advances in immunotherapy have made an unprecedented leap in treating colorectal cancer (CRC). However, more effective therapeutic regimes need a deeper understanding of molecular architectures for precise patient stratification and therapeutic improvement. We profiled patients receiving neoadjuvant chemotherapy alone or in combination with immunotherapy (PD-1 checkpoint inhibitor) using Digital Spatial Profiler (DSP), a high-plex spatial proteogenomic technology. Compartmentalization-based high-plex profiling of both proteins and mRNAs revealed pronounced immune infiltration at tumor regions associated with immunotherapy treatment. The protein and the corresponding mRNA levels within the same selected regions of those patient samples correlate, indicating an overall concordance between transcriptional and translational levels. An elevated expression of PD-L1 at both protein and mRNA levels was discovered in the tumor compartment of immunotherapy-treated patients compared with chemo-treated patients, indicating potential prognostic biomarkers are explorable in a spatial manner at the local tumor microenvironment (TME). Elevated expression of PD-L1 was verified by immunohistochemistry. Other compartment-specific biomarkers were also differentially expressed between tumor and stromal regions, indicating a dynamic interplay that can potentiate novel biomarker discovery from TME perspectives.